PENYULUHAN EFEKTIFIKTAS STRETCHING DI SELA WAKTU KERJA TERHADAP PENURUNAN INTENSITAS KELELAHAN PADA PEKERJA DI PT JS - Lira Mufti Azzahri Isnaeni; Etri Gustriana (Universitas Pahlawan Tuanku Tambusai, 2021)
Stretching is an exercise to maintain and develop flexibility or flexibility. There are many people who still do not understand stretching between work hours to reduce fatigue intensity. The implementing team is a lecturer with an educational background of S1 Public Health. The implementation team is expected to be able to provide solutions to student problems. Health efforts for each individual need to be maintained and improved wherever the individual is, not least in the workplace, because in the workplace there are various factors that cause work accidents caused by work fatigue. Counseling on the Effectiveness of Stretching Between Work Time on Reducing the Intensity of Fatigue in Workers at PT JS. The aim is to increase the knowledge of workers regarding stretching activities during working hours to prevent work accidents. Interventions stretching (stretching muscles) on the sidelines of work can be done for 10-15 minutes with 16 exercises for each participant, and is expected to be able to restore the freshness of worker participants, increase work concentration, stimulate worker creativity. So that the risk of accidents caused by work fatigue can be avoided. The development method to be implemented is a series of stages that are arranged systematically. Keywords : Stretching ; education